2020
DOI: 10.1042/bsr20193532
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLX6-AS1 as a potential molecular biomarker in the clinicopathology and prognosis of various cancers: a meta-analysis

Abstract: Objective: Recent studies have shown that distal-less homeobox 6 antisense 1 (DLX6-AS1) is aberrantly expressed in various cancers and is associated with poor prognosis. This meta-analysis is designed to investigate the effects of DLX6-AS1 expression on clinicopathological features and survival outcomes. Methods: All eligible studies were searched from Pubmed, Web of Science, Embase, the Cochrane Library, and Wanfang database, up to August 2019. The literature was selected according to the inclusion and exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Colorectal cancer is a major neoplasm of the digestive tract, which has a high morbidity and mortality rate in China [1]. In recent years, with the change in environment and living habits, the incidence of colorectal cancer has seen a significant upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is a major neoplasm of the digestive tract, which has a high morbidity and mortality rate in China [1]. In recent years, with the change in environment and living habits, the incidence of colorectal cancer has seen a significant upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…Two transcripts, DLX6 antisense RNA 1 ( DLX6-AS1 ) and protocadherin 8 ( PCDH8 ), fulfilled these criteria. DLX6-AS1 represents a long non-coding RNA that has a predictive value in various cancers ( Tian et al, 2020 ). PCDH8 , in turn, encodes a transmembrane adhesion and signaling molecule that acts as a tumor suppressor ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have shown that lncRNAs were abnormally expressed in various cancers, and function as oncogene or tumor suppressor based on these expression level, participate in the initiation and progression of cancer. Previous meta-analyses have indicated that DLX6-AS1 [ 40 ], PVT1 [ 41 ], SNHG15 [ 22 ] and GHET1 [ 24 ] are related to the clinicopathological features and prognosis of various cancers. These evidences indicated that lncRNA may be a specific prognostic biomarker and therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%